High–resolution study of the tetradecad stretching vibrational bands of MSiD4 (M=28, 29, 30). (October 2019) - Ulenikov, O.N.; Gromova, O.V.; Bekhtereva, E.S.; Raspopova, N.I.; Kuznetsov, A.V.; Sydow, C.; Bauerecker, S.
Highlights: High-resolution spectra of SiD4. Tetradecad bands of SiD4. Resonance interactions in spherical top molecules. Determination of spectroscopic parameters. Abstract: The infrared spectra of SiD4 isotopologues with the abundances of 92.23 % for 28 SiD4, 4.68 % for 29 SiD4, and 3.09 % for 30 SiD4 were measured in the region of 3020–3260 cm − 1 with a Bruker IFS 120HR Fourier transform spectrometer and analysed. For 28 SiD4 1473 transitions with J max = 36 were assigned to the tetradecad stretching bands ν 1 + ν 3 ( F 2 ), 2 ν 3 ( F 2 ) and 2 ν 3 ( E ). Rotational, centrifugal distortion, tetrahedral splitting, and interaction parameters were determined from the fit of experimental line positions. A set of 31 parameters, obtained from the fit, reproduces the initial experimental data with the d rms = 3.5 × 10 − 4 cm − 1 which is close to experimental uncertainty. The results of the analogous analyses for the ν 1 + ν 3 band of the 29 SiD4 and 30 SiD4 isotopologues are also presented with 199 and 169 assigned transitions. A list of experimental transitions is presented as a Supplementary material part.